2022
DOI: 10.18087/cardio.2022.11.n2262
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tachycardia-induced cardiomyopathy in patients with first-time decompensation of chro­nic heart failure with reduced left ventricular ejection fraction of nonischemic etiology and persistent atrial tachyarrhythmia

Abstract: Aim    To identify possible predictors of tachycardia-induced cardiomyopathy (TICMP) in patients with newly developed decompensated chronic heart failure (CHF) of nonischemic origin with reduced left ventricular ejection fraction (LV EF) and with persistent atrial tachyarrhythmias. Material and methods    This study included 88 patients with newly developed decompensated CHF of nonischemic origin with reduced LV EF and persistent atrial tachyarrhythmias. Resting 12-lead electrocardiography (EGC) and transthora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Similar results were obtained in another study including 88 patients with newly diagnosed LV systolic dysfunction and tachyarrhythmias. It was shown that a smaller volume and lower LV myocardial mass distinguished patients with TIC from patients with DCM [33]. In the present CMR-derived data, the TIC patients had a significantly lower LVEDV.…”
Section: Discussionsupporting
confidence: 43%
“…Similar results were obtained in another study including 88 patients with newly diagnosed LV systolic dysfunction and tachyarrhythmias. It was shown that a smaller volume and lower LV myocardial mass distinguished patients with TIC from patients with DCM [33]. In the present CMR-derived data, the TIC patients had a significantly lower LVEDV.…”
Section: Discussionsupporting
confidence: 43%
“…The ECG often shows a Q wave in the inferior and lateral leads, changes in the P wave (due to enlargement of one or both atria; enlargement of the right atrium) and the presence of electrocardiographic signs of left ventricular hypertrophy, sinistrograms, and deep negative T waves from V2 to V4 which are highly suggestive of the diagnosis of HCM. Echocardiographic left ventricular wall thickening ≥ 15 mm is significant for HCM (≥ 13 mm for patients with a positive family history of HCM) 13 . A gradient over LVOT > 30 mmHg is associated with clinical symptoms, and > 50 mmHg is an indication for surgical treatment.…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%
“…In professional athletes, it is necessary to distinguish between the existence of an athletic heart. It should be noted that the cardiac chambers are larger in the athletic heart, while an end-diastolic left ventricular diameter < 54 mm is associated with HCM 13 .…”
Section: Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%